Building a Genomics-Informed Nursing Workforce: Recommendations for Oncology Nursing Practice and Beyond - Jacqueline Limoges; Rebecca Puddester; Andrea Gretchev; Patrick Chiu; Kathy Calzone; Kathleen Leslie; April Pike; Nicole Letourneau (Current Oncology)
Background: Genomics is a foundational element of precision health and can be used to identify inherited cancers, cancer related risks, therapeutic decisions, and to address health disparities. However, there are structural barriers across the cancer care continuum, including an underprepared nursing workforce, long wait times for service, and inadequate policy infrastructure that limit equitable access to the benefits of genomic discoveries. These barriers have persisted for decades, yet they are modifiable. Two distinct waves of efforts to integrate genomics into nursing practice are analyzed. Drawing on research and observations during these waves, this discussion paper explores additional approaches to accelerate workforce development and health system transformation. Results: Three recommendations for a third wave of efforts to integrate genomics are explored. (1) Collaborate across the domains of nursing practice, professions, and sectors to reset priorities in response to emerging evidence, (2) Education in leadership, policy and practice for rapid scale-up of workforce and health system transformation, and (3) Create a research framework that generates evidence to guide nursing practice. Conclusions: Preparing nurses to lead and practice at the forefront of innovation requires concerted efforts by nurses in all five domains of practice and can optimize health outcomes. Leveraging nursing as a global profession with new strategies can advance genomics-informed nursing.